Breast cancer patients have lower in-hospital mortality after acute coronary syndrome, a 5 year nationwide analysis. (25th November 2020) - Huang Lucas, C; Yue, B; Wei, X; Wu, L; Abed, R; Bachoo, N; Lopes, J; Isath, A; Narasimhan, B; Contreras, J
Abstract: Background: Breast cancer and cardiovascular disease (CVD) share common risk factors, and breast cancer therapies are well known to cause cardiotoxicity. Prior studies highlighted the higher burden coronary artery disease and the importance to further assess its consequences on breast cancer patients. Purpose: We sought to evaluate the revascularization rate and in-hospital short-term outcomes of breast cancer patients following acute coronary syndrome (ACS) compared to the general female population. Methods: We reviewed the Nationwide Inpatient Sample from 2010 to 2014 to identify female patients with principal diagnosis of ACS (ST-elevation and non ST-elevation myocardial infarction, and unstable angina). Two subgroups were identified, women with a history of breast cancer and women without, and were propensity matched. Multivariate regression analyses were performed to evaluate the impact of breast cancer on primary outcome (in-hospital mortality) and secondary outcomes: occurrence of shock, acute kidney injury (AKI), mechanical ventilation (MV), and length of stay (LOS). We also compared the rate of cardiac procedures. Statistical significance of odd ratios (OR) is defined with p-value<0.05 and reported 95% confidence intervals (CI). Results: We identified a total of 245, 563 female patients with primary diagnosis of ACS, among them 10, 625 (4.3%) had a history of breast cancer. The comorbidity of breast cancer was associated with statistically significant lower rates of mortality (OR 0.83, CI 0.74–0.94), shock (OR 0.87, CI 0.77–0.99), AKI (OR 0.90, CI 0.82–0.98), MV (OR 0.81, CI 0.71–0.92) and relative 5.4% decrease in LOS (CI: −7.8%, −3.0%). The cardiac procedural rates were similar for left heart catheterization (OR 0.96, CI 0.90–1.02), for percutaneous coronary intervention (OR 0.95, CI 0.89–1.02) and for CABG (OR 0.88, CI 0.78–1.00) compared to control group. Conclusion: Breast cancer patients received a comparable catheterization and revascularization procedure rate and exhibited a statistically significant lower morbidity and mortality rates during hospitalization after an ACS event compared to the general female population. Funding Acknowledgement: Type of funding source: None